Host Genetics of Cytomegalovirus Pathogenesis - Sezgin, Efe; An, Ping; Winkler, Cheryl A. (Frontiers in Genetics, 2019)
Human cytomegalovirus (HCMV) is a ubiquitous herpes virus (human herpes virus 5) with the highest morbidity and mortality rates compared to other herpes viruses. Risk groups include very young, elderly, transplant recipient, and immunocompromised individuals. HCMV may cause retinitis, encephalitis, hepatitis, esophagitis, colitis, pneumonia, neonatal infection sequelae, inflammatory and age-related diseases. With an arsenal of genes in its large genome dedicated to host immune evasion, HCMV can block intrinsic cellular defenses, and interfere with cellular immune responses. HCMV also encodes chemokines, chemokine receptors, and cytokines. Therefore, genes involved in human viral defense mechanisms and those encoding proteins targeted by the CMV proteins are candidates for host control of CMV infection and reactivation. Although still few in number, host genetic studies are producing valuable insights into biological processes involved in HCMV pathogenesis and HCMV related diseases. For example, genetic variants in the immunoglobulin GM light chain can influence the antibody responsiveness to CMV glycoprotein B, and modify risk of HCMV related diseases. Moreover, CMV infection following organ transplantation has been associated with variants in genes encoding toll-like receptors (TLRs), programmed death-1 (PD-1), interleukin-12p40 (IL-12B). A KIR haplotype (2DS4+) is proposed to be protective for CMV activation among hematopoietic stem cell transplant patients. Polymorphisms in the interferon lambda 3/4 (IFNL3/4) region are shown to influence susceptibility to CMV replication among solid organ transplant patients. Interestingly, the IFNL3/4 region is also associated with AIDS-related CMV retinitis susceptibility in HIV infected patients. Likewise, interleukin-10 receptor 1 (IL-10R1) variants are shown to influence CMV retinitis development in patients with AIDS. Results from genome-wide association studies suggest a possible role for microtubule network and retinol metabolism in anti-CMV antibody response.